Diseño y aplicación de una guía de actividades lúdicas dirigida a docentes y padres de familia, para fomentar el Buen Vivir en la Escuela “Miguel de Cervantes” de la comunidad de Alpamálag de Acurios, cantón Pujilí, provincia de Cotopaxi año lectivo 2012-2013 - Calvopiña Monge, Mónica del Pilar (2015)
The recreational activities promote self-confidence, autonomy and formation of personality; thus becoming one of the main recreational and educational activities for Living. The game is an activity that is used for fun and enjoyment of the participants, in many cases, even as a social tool for those in the educational environment of students. The practice of recreational activities turn provides the Good Life is nothing but live fully, participatory, in harmony and balance with himself and the community. This research as a case study based education for the good life, with the active participation of parents and teachers supported in traditional games that are gradually becoming outdated. Education and the Good Life act in two ways. On the one hand, the right to education is an essential component of good living, allowing the development of human potential, and as such, guarantees equal opportunities for all people. Moreover, the Good Life is a priority area of education, to the extent that the educational process should include the preparation of future citizens, values and knowledge to promote activities that integrate, assess and reinforce student learning. An investigation of the theoretical issues that informed the process and subtopics of each variables addressed in the study was structured. The research used was descriptive, theoretical and statistical methods, the unit of study was made to teachers and parents on the basis of surveys and interviews. For the operationalization of the variables was performed: identification, conceptual definition, operational definition and signaling indicators.